BAHASA INDONESIA DI AMBANG KRISIS: STUDI DIAGNOSTIK ATAS RENDAHNYA KOMPETENSI BERBAHASA DI SDN BANYIOR 2 - Nur Fadilah; Abdussalam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify low Indonesian language proficiency among fifth-grade students of Banyior 2 Elementary School. Indonesian is crucial for communication and education at the elementary school level. However, field observations indicate that students struggle with listening, speaking, reading, and writing skills. This study employed a qualitative method with a case study approach. Information was collected through observation, interviews, and diagnostic assessments, and assessed using an interactive model proposed by Miles and Huberman. The results indicate that both internal factors (such as lack of motivation, minimal interest, and inappropriate learning methods) and external factors (such as the prevalence of lecture-based teaching, inadequate learning resources, lack of social support, and inadequate parental involvement) contribute to poor language proficiency. These findings emphasize the importance of engaging teaching methods, the use of creative learning resources, and a supportive learning environment.